2022
DOI: 10.1002/arp.1885
|View full text |Cite
|
Sign up to set email alerts
|

Integrating spatial and legacy data to understand archaeological sites in their landscape. A case study from Unguja Ukuu, Zanzibar

Abstract: Spatial analysis is paramount for understanding, monitoring, and conserving ancient settlements and cultural landscapes. Advancing remote sensing and prospection techniques are expanding the methodological frame of archaeological settlement analysis by enabling remote, landscape-scale approaches to mapping and investigation. Whilst particularly effective in arid lands and areas with sparse or open ground cover, such as vegetation and buildings, these approaches remain peripheral in tropical environments becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Research on the Swahili Coast has definitively revealed the scale, complexity, and interconnectedness of non-elite, rural settlement (Kusimba et al 2013;LaViolette and Fleisher 2018). Increasingly, archaeologists have sought to investigate the environmental dynamics of Swahili settlement landscapes (Faulkner et al 2022;Fitton et al 2023;Kotarba-Morley et al 2022;Pawlowicz et al 2014;Prendergast et al 2017;Quintana Morales et al 2022;Walshaw and Stoetzel 2018). This paper contributes to this growing body of research by modeling and testing the environmental affordances that influenced regional settlement trends.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research on the Swahili Coast has definitively revealed the scale, complexity, and interconnectedness of non-elite, rural settlement (Kusimba et al 2013;LaViolette and Fleisher 2018). Increasingly, archaeologists have sought to investigate the environmental dynamics of Swahili settlement landscapes (Faulkner et al 2022;Fitton et al 2023;Kotarba-Morley et al 2022;Pawlowicz et al 2014;Prendergast et al 2017;Quintana Morales et al 2022;Walshaw and Stoetzel 2018). This paper contributes to this growing body of research by modeling and testing the environmental affordances that influenced regional settlement trends.…”
Section: Discussionmentioning
confidence: 99%
“…In African archaeology, recent studies have used a combination of remote sensing and spatial analysis for site detection, predictive modeling, and for understanding archaeological landscapes (Biagetti 2017;Davis and Douglass 2021;Fitton et al 2023Harrower et al 2020Klehm et al 2019;Ochungo et al 2022;Pawlowicz et al 2020;Reid 2016Reid , 2020Thabeng et al 2020). Creating models for site detection with multispectral imagery is increasingly accessible, with resources like Landsat, Planet, and Sentinel 2 imagery becoming available at increasingly high spatial, spectral, and temporal resolutions.…”
Section: Predictive Modeling Zonal Statistics and Archaeological Pros...mentioning
confidence: 99%
See 2 more Smart Citations